Ciberseguridad y arbitraje internacional: el Protocolo de Ciberseguridad en Arbitraje Internacional del ICCA, el NYC Bar y el CPR (Edición 2020) - Fernández-Samaniego, Javier (2020)
The Protocol on Cybersecurity in International Arbitration constitutes an innovative proposal providing a rigorous approach aimed towards raising awareness on cybersecurity risks in arbitration for its participants. Likewise, it seeks to be a guide to which the parties and arbitrators can recur in order to determine which cybersecurity measures can reasonably be adopted. The Protocol is a soft-law instrument that acknowledges cybersecurity measures may vary for each particular case.In this article, the authors evaluate the innovations proposed in the Protocol’s 2020 edition. Thus, they address its evolution, reviewing the newest types of cyber threats, previous regulatory efforts and, in greater detail, the principles and schedules proposed in this document. Finally, the authors also reflect on the opportunities that the Protocol provides in a global emergency situation due to the COVID-19 pandemic.